EXPLORATION OF THE RELATIONSHIP BETWEEN EMPLOYER BRANDING, SOCIAL MEDIA ENGAGEMENT, AND WORK VALUE ALIGNMENT ON JOB APPLICATION PREFERENCES AT ALFAMART RETAIL IN BANDAR LAMPUNG CITY - Aida Royani; Euis Mufahamah; Harold Kevin Alferdo (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the influence of employer Branding and social media engagement on job application preference, with work value congruence as a moderating variable among generation Z and millennial potential employees. increasing labor market competition in the digital era encourages retail companies, such as Alfamart, to strengthen organizational attractiveness through effective branding strategies and digital communication. This research employs a quantitative approach using a survey method involving final-year students and job seekers from generation Z and millennial groups in Bandar Lampung City. Data were collected using Likert-scale questionnaires and analyzed using SmartPLS through measurement model and structural model evaluations. The findings indicate that employer branding, social media engagement, and work value congruence have a positive influence on job application preference. In addition, work value congruence strengthens the relationship between employer branding and job application preference. These results suggest that a strong corporate image, active social media interaction, and alignment between individual and organizational values play an important role in increasing the intention of generation Z and millennials to apply for jobs. This study supports the Organizational Attractiveness theory, which emphasizes the importance of organizational image, digital communication, and value congruence in attracting potential employees.